(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Early recognition and diagnosis of neonatal sepsis are difficult because of the variable and non-specific clinical presentation of this condition. It is extremely important to make an early diagnosis of neonatal sepsis for prompt institution of antimicrobial therapy. So the objective of the study was to evaluate the efficacy of serum procalcitonin as a reliable marker in diagnosis of neonatal sepsis. Methodology: This cross sectional analytical study was carried out in the Special Care Baby Unit of a tertiary level care hospital in Bangladesh from September 2012 to May 2013. Total 75 newborn with suspected sepsis were included in the study. Specimens of blood were obtained from each neonate prior to commencement of antibiotic for sepsis work up. Serum CRP and procalcitoninlevels were measured. The data from blood cultures were used as the gold standard to evaluate the optimum sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and area under the Receiver Operative Characteristic (ROC) curves. Results:Among total 75 newborns included in this study, 49.3% (37) newborn were diagnosed as proven sepsis and 50.7% (38) newborn as clinical sepsis.The procalcitonin (PCT) was high in 58.7% (500-<2000 pg/ml) newborn and remarkably high (2000-<10000) in 36% newborn with sepsis. At a cut-off value > 500pg/ml, the sensitivity of PCT in detecting sepsis was 48.6%, its specificity 76.3%, positive predictive value was 66.7%, and negative predictive value was 60.4% whereas the sensitivity of CRP for predicting sepsis was 35.1%, specificity 78.9%, positive predictive value 61.9% and negative predictive value was 55.6%. The area under the ROC curve for procalcitonin(0.653) was significantly higher than CRP (0.571). Conclusion:Serum PCT was superior to serum CRP level in terms of early diagnosis of neonatal sepsis, in detecting the severity of sepsis. PCT is a reliable marker than CRP in the diagnosis of neonatal sepsis. Bangladesh J Child Health 2018; VOL 42 (1) :19-25